Routing issues and challenges in Underwater Wireless Sensor Networks - Sarao, Pushpender; Chattu, Kannaiah; Swapna, (International Journal of Computer Sciences and Engineering, 2025)
Sensor networks in underwater environments, that is, forming underwater wireless sensor networks (UWSNs), has been attracted significant attention recently from both academia and industry. The characteristics of underwater sensor networks are fundamentally different from that of terrestrial networks. In this paper, we overviewed the main routing issues and challenges for efficient communications in underwater acoustic sensor networks.